Development of a tree shrew-specific interferon-gamma assay. Issue 2 (4th March 2018) - Zhang, Xuemei; Xu, Jingwen; Wu, Zhongxiang; Zhu, Wenbing; Dong, Shaozhong
ABSTRACT: Tree shrews ( Tupaia belangeri ) are small squirrel-like mammals closely related to primates. Due to their susceptibility to several human viruses, tree shrews have been proposed as potential animal models for the study of human viral infections. However, there are no standardized assays currently available for the detection of tree shrew-specific interferon (IFN)-γ, a major cytokine secreted during the antiviral immune response. Herein, we developed a novel enzyme-linked immunosorbent assay (ELISA) for the quantification of IFN-γ in tree shrew serum samples. Tree shrew-specific IFN-γ was expressed in Escherichia coli via fusion with glutathione S-transferase (GST-TS-IFN-γ) to obtain recombinant IFN-γ. To generate anti-IFN-γ monoclonal antibodies, mice were immunized with the GST-TS-IFN-γ recombinant fusion protein, and hybridoma cell lines were established. Similarly, anti-IFN-γ polyclonal antibodies were obtained from immunized rabbits, purified, and conjugated to horseradish peroxidase (HRP). Based on the results obtained from the antibody matching test, we optimized the monoclonal antibody (1:2000) and the HRP-conjugated polyclonal antibody (1:8000) as coating and detection antibodies, respectively. Titration curves were generated with recombinant IFN-γ to develop a sensitive sandwich ELISA; the lowest detection limit of the assay was 20 ng/mL. We also tested mitogen-stimulated tree shrew blood samples in this ELISA, and found significantly higher levels of IFN-γ in the stimulated versus the unstimulated samples. Most importantly, our ELISA system detected native IFN-γ in serum samples from 50 healthy tree shrews. We have thus developed a novel ELISA, and have demonstrated the first ELISA-based measurement of IFN-γ in tree shrew serum samples.